(untitled) (American Journal of Technology and Applied Sciences, 2026)
This article analyzes the role and importance of artificial intelligence (AI) in improving the functioning of the cardiovascular system. It highlights the application of AI technologies in the field of cardiology, particularly in early disease detection, accurate diagnosis, real-time monitoring, and the development of personalized treatment strategies. Furthermore, the study examines how AI can process large volumes of medical data and predict the risk of cardiovascular diseases, thereby enhancing the effectiveness of preventive measures. The article also discusses the role of AI-based systems in improving the quality of healthcare, along with the challenges associated with their implementation, including data security, privacy, regulatory compliance, and the need for specialized training of medical professionals.